A Case Report of Embryonal Botryoid Rhabdomyosarcoma of the Uterine Cervix in a 26- Year-Old Woman - Gunel Ziyadova; Altan Kavuncuoglu; Gonca Ozten; Zafer Selcuk Tuncer (Gynecology Obstetrics & Reproductive Medicine)
Botryoid rhabdomyosarcoma originating from the cervix is rare among fertile women and constitutes 0.2% of all uterine cancers. A 26-year-old female patient with a cervical polyp presented with a case of sarcoma botryoides. The biopsy specimen confirmed the botryoid sarcoma of the uterine cervix and the patient underwent definitive surgery with lymphadenectomy. Pathology showed negative margins and total extraction of tumor. The tumor was confined to the cervix. The patient is considered group 1A in Intergroup RMS Working Group V (IRSG) criteria and the treatment plan continued with adjuvant vincristine, actinomycin D, cyclophosphamide chemotherapy.